Sanctum of the soul - Kade, Kel (Kade, Kel. Shroud of prophecy, 2025)
"The chosen one is dead, the powerful have abandoned their subjects, and Death has come for them all. Aaslo, the reluctant new Chosen One, and Teza, a failed magus healer, lead a small group of broken people who continue to hold back the tide of a war between the gods. They gather what forces they can scrape together for a final battle. Their band of unlikely warriors' grit and bravery in the face of staggering odds, however, has strengthened all of them as they come into their power and their destiny. Aaslo stands at a crossroad where he must embrace all of what he has become even in the face of losing the war, his friends, and his world."--Inside front jacket flap.